Teaching Massive, Open, Online, Courses (MOOCs): Tales from the Front Line - Lowenthal, Patrick; Snelson, Chareen; Perkins, Ross (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Very little research has been conducted about what it is like to teach a MOOC. Given this, a mixed methods study, involving a survey of 186 MOOC instructors and 15 follow-up interviews, was conducted to explore the motivation, experiences, and perceptions of instructors who have taught massive open online courses. Findings indicate that instructors were motivated to teach MOOCs for three main reasons: (1) interest and passion, (2) publicity and marketing, or (3) benefits and incentives. Most instructors had little online teaching experience prior to teaching their first MOOC, but were satisfied with the experience. The majority believed their own MOOC provided a high quality learning experience but thought that MOOCs overall might not be as good as face-to-face courses. Concerns were raised about the future of MOOCs for online learning.